Market Perspective Determinants for Stock Returns in Manufacturing Companies on the IDX - Widianingtyas, Rifa Pramesti; Irawati, Zulfa (Prosiding University Research Colloquium, 2022)
he purpose of this study was to analyze the effect of Economic Value Added (EVA), Price toBook Value (PBV), Earning Per Share (EPS) on stock returns. This study uses a quantitativedescriptive method. The data sources used are secondary data sources, in the form offinancial report data from food and beverage manufacturing sector companies listed on theIndonesia Stock Exchange from 2019-2021 and annual reports. The object of this researchis a food and beverage manufacturing company that is listed on the IDX in 2019-2021. Theanalytical method used is descriptive statistical analysis, classic assumption test, namely:normality test, multicollinearity test, autocorrelation test and heteroscedasticity test andmultiple linear regression analysis. Then do the t test and F test. Data collection techniquesusing purposive sampling method. The results in this study partially, Economic ValueAdded (EVA) and Earning Per Share (EPS) have a positive and significant effect on stockreturns. While simultaneously Economic Value Added (EVA), Price to Book Value (PBV) andEarning Per Share (EPS) together influence stock returns.